Design and Implementation of FPGA-based Systolic Array for LZ Data Compression - El ghany, Mohamed A. Abd; Salama, Aly E.; Khalil, Ahmed H. (2007 IEEE International Symposium on Circuits and Systems (ISCAS), 2007)
Hardware Implementation of Data compression algorithms is receiving increasing attention due to exponentially expanding network traffic and digital data storage usage. Among lossless data compression algorithms for hardware implementation, Lempel -Ziv algorithm is one of the most widely used. The main objective of this paper is to enhance the efficiency of systolic- array approach for implementation of Lempel- Ziv algorithm. The proposed implementation is area and speed efficient. The compression rate is increased by more than 40% and the design area is decreased by more than 30%. The effect of the selected buffer's size on the compression ratio is analyzed. An FPGA implementation of the proposed design is carried out. It verifies that data can be compressed and decompressed on-the-fly.